Effects of calcium–magnesium carbonate and calcium–magnesium hydroxide as supplemental sources of magnesium on microbial fermentation in a dual-flow continuous culture - Arce Cordero, José Alberto (2020)
La Universidad de Costa Rica apoyó el programa de doctorado de José Alberto Arce Cordero